Report World War II (New York, NY, 1995)
The reporting also takes us into the Pacific and gets us down with those doing the actual work of the war including Annalee Jacoby's account of nurses under fire in Bataan. We get early reporting on the Japanese Internment camps and the Holocaust with the NY Times reporting in 1942 that one million Jews reported slain.
Keywords: Journalism,World War, 1939 - 1945; History,Press coverage; 20th century; United States,United States